DESIGN OF WHEEL ROBOT TO DETECT ANTI-TANK MINES BASED ON NRS MUDA METHODS - Nur Rachman Supadmana Muda; Bilqis Faranadila; M.Faisal Fadilah (Journal of Innovation Research and Knowledge, 2024)
The purpose of this research is to design a robot technology equipped with anti-tank mine detector components. The current anti-tank mine detectors still use personnel to detect the presence of mines. This is considered inefficient because it takes a long time, if not careful it can explode personnel or operators so that the risk factor is very high. Therefore, a robot system is needed that is equipped with a mine detector that can be used to detect mines replacing human tasks, so that the risk factor becomes low and safe. The technology used in the robot is a detector, a transmit-receive control system at a frequency of 563 MHz, a control distance of up to 1km, equipped with GPS so that it can provide information about the presence of mines and inform the controller where the position of the mine is. The method used with NRS MUDA technology is a real-time detection method that directly plots coordinate data where the mine is located and is given a special red marking